2008
DOI: 10.1007/s10750-007-9262-3
|View full text |Cite
|
Sign up to set email alerts
|

A short review of pike ecology

Abstract: A brief review is provided in some advances in understanding the ecology of pike Esox lucius Linnaeus over the last 10 years. Based on longterm studies and manipulative, often short-term experiments (laboratory, field and mesocosms) several established theories have been supported, as well as new concepts developed. Despite their wide distribution pike show low levels of polymorphism and divergence indicative of a recent common ancestral population. Recent genetic studies, however, indicate a single refugium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 100 publications
(106 reference statements)
6
122
0
2
Order By: Relevance
“…In recent years, reproduction of Ide in captivity has received increasing attention to meet the demand of high quality juveniles for restocking (Wojda, 2004;Krejszeff et al, 2009), sport fishing, aquarium industry (JamrĂłz et al, 2008;Cejko et al, 2010), toxicity studies (Witeska et al, 2014) and as a bio-monitoring agent (Fenske et al, 2006). On the other hand, Northern pike is an iteroparous, large-bodied and long-living (>10 years) fish species inhabiting the northern hemisphere (Craig, 2008;Forsman et al, 2015). There is interest in fishing this species but it has also been cultivated extensively in Europe and Asia since the middle ages (Steinberg, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, reproduction of Ide in captivity has received increasing attention to meet the demand of high quality juveniles for restocking (Wojda, 2004;Krejszeff et al, 2009), sport fishing, aquarium industry (JamrĂłz et al, 2008;Cejko et al, 2010), toxicity studies (Witeska et al, 2014) and as a bio-monitoring agent (Fenske et al, 2006). On the other hand, Northern pike is an iteroparous, large-bodied and long-living (>10 years) fish species inhabiting the northern hemisphere (Craig, 2008;Forsman et al, 2015). There is interest in fishing this species but it has also been cultivated extensively in Europe and Asia since the middle ages (Steinberg, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Even if we did not show any effect of WLF on adult perch habitat preference, they could act differently on other species such as pike, a more demanding species in terms of spawning substrate (Craig, 2008). Very recently, Cooke et al (2016) submitted that: "quantifying and describing the spatial ecology of fish and their habitat is an important component of freshwater fishery assessment and management".…”
Section: Seasonal Pattern Of Habitat Use and Preferencementioning
confidence: 81%
“…Tatrai et al [105] have reported multiyear control of phytoplankton by keeping cyprinid fish populations around 100 kg/ha with piscivore populations sustained at a biomass ratio > 15% and total fish biomass < pike. Vegetation provides a spawning habitat that contributes to spawning success and survival of young [19].…”
Section: Professional Expertisementioning
confidence: 99%